A New Approach for Environmental Risk Assessments of Living Modified Organisms in South Korea - Su-Hyang Yoo; Young Jun Jung; Jung Ro Lee (Applied Sciences, 2022)
As the development and use of living modified organisms (LMOs) steadily increase, new risk assessment methods that reflect domestic natural ecosystems are being developed. Although LM plants are fundamentally necessary for environmental risk assessment, the introduced gene products and LMO proteins can replace transgenic plants. However, their use is problematic because of instability and indirect assessment data issues. This study proposes a risk assessment tool and scheme for introducing LMO proteins into genetically modified crops. The agroinfiltration method for transient LMO gene expression in plants is a practical tool which can be used to rapidly verify the putative risks of LMO proteins against insects using an LM crop mimic plant with a stably expressed LMO protein. This study used Nicotiana tabacum leaves, which transiently but stably expressed the insecticidal LMO protein Vip3Aa, for LMO risk assessments against Spodoptera litura. The Vip3Aa protein was stably expressed for 5 d in the agroinfiltrated plants, and the protein was active against target insects for environmental LMO risk assessments. In the toxicity evaluation of Vip3Aa-expressing plants against S. litura, the number of deaths was higher in the Vip3Aa-infiltrated N. tabacum-fed group than that in the recombinant Vip3Aa-fed group. In addition, the cumulative number of deaths in the infiltration leaf-fed group was approximately 12-fold higher than that in the protein-fed group under low dosage conditions. This study aimed to develop a transient expression model which can be used to evaluate whether the overall risk of LMO protein is acceptable for use. These results support the usefulness of the transient expression model using an agroinfiltration method as a rapid risk validation tool for LMO proteins against herbivorous insects before producing transgenic plants.